White light emission from a polymer bilayer by incomplete cascade energy transfer - Park, J.H.; Park, O.O.; Kim, Jai Kyeong; Yu, Jae Woong; Kim, Y.C. (한국물리학회, 2006)
White light emission was obtained from a light-emitting diodes (LEDs) prepared from an immiscible polymer blend consisting of poly(9,9′-dihexylfluorene-2,7-divinylene-m-phenylenevinylene-stat-p-phenylenevinylene) (PDHFPPV) and poly(2-methoxy-5-(2′-ethy-hexyloxy)-1,4-phenylenevinylene) (MEH-PPV). An inefficient energy transfer between PDHFPPV and MEH-PPV was observed because the blends are partially miscible. More importantly, because the order of bandgap energy is PVK > PDHFPPV > MEH-PPV we observed pure and strong white emission from this PLEDs, which results from the efficient F？rster-type energy transfer from PVK to PDHFPPV and the partial energy transfer from PDHFPPV to MEH-PPV. The ITO/(PVK/immiscible blend)/Li:Al devices showed more enhanced white-light output compared with that of the ITO/(immiscible blend)/Li:Al device. ？ 2005 Elsevier B.V. All rights reserved.